Dekonstruksi Derrida dan Pengaruhnya pada Kajian Pangan - Muhammad Syafri; Arlin Adam; Syamsu A. Kamaruddin (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Deconstruction was introduced by a French philosopher born in Algeria, Jacques Derrida. This theory challenges the centralized and rounded mode of meaning as might be desired by the text or which is deliberately made clear by the logical relationship of the text. The “unspeakable” power of the text is the logic that is trivialized or underestimated as a secondary meaning that at times endangers the structure of the text or produces ambiguous paradoxes, which will erode the reader. Deconstruction aims to dismantle the Western metaphysical tradition such as Husserlin's phenomenology, Saussurean structuralism, structuralism. Derrida's deconstruction method is better known as metaphorical deconstruction. Metaphor here is not understood as an aspect of the expressive function of language but as an essential condition of speech. Metaphor represents one way of constructing discourse and strongly influences the understanding of various texts. Deconstruction is carried out on metaphorical texts composed by the author. Deconstruction can occur in the text itself or vice versa, we who deconstruct a text. In conclusion, deconstruction can be applied in everyday life by recognizing that other people's views on a topic and perspective may have different meanings from ours.